2021
DOI: 10.1083/jcb.201909139
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy facilitates mitochondrial rebuilding after acute heat stress via a DRP-1–dependent process

Abstract: Acute heat stress (aHS) can induce strong developmental defects in Caenorhabditis elegans larva but not lethality or sterility. This stress results in transitory fragmentation of mitochondria, formation of aggregates in the matrix, and decrease of mitochondrial respiration. Moreover, active autophagic flux associated with mitophagy events enables the rebuilding of the mitochondrial network and developmental recovery, showing that the autophagic response is protective. This adaptation to aHS does not require Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
8
28
0
Order By: Relevance
“…Heat stress was previously found to cause increased mitochondrial fragmentation in muscles (Momma et al , 2017; Machiela et al , 2020; Chen et al , 2021), and disrupting mitochondrial fission and fusion were detrimental and beneficial to heat stress resistance respectively, suggesting that mitochondrial fragmentation is mechanistically important for thermoresistance (Machiela et al , 2020). Given the muscle-enriched expression of W06A11.1 (Fox et al , 2007), and that neuronal signaling can induce distal mitochondrial fragmentation in muscles (Burkewitz et al , 2015; Zhang et al , 2019), we wondered if neuronal HLH-30/TFEB mediates thermoresistance through W06A11.1-dependent muscle mitochondrial fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Heat stress was previously found to cause increased mitochondrial fragmentation in muscles (Momma et al , 2017; Machiela et al , 2020; Chen et al , 2021), and disrupting mitochondrial fission and fusion were detrimental and beneficial to heat stress resistance respectively, suggesting that mitochondrial fragmentation is mechanistically important for thermoresistance (Machiela et al , 2020). Given the muscle-enriched expression of W06A11.1 (Fox et al , 2007), and that neuronal signaling can induce distal mitochondrial fragmentation in muscles (Burkewitz et al , 2015; Zhang et al , 2019), we wondered if neuronal HLH-30/TFEB mediates thermoresistance through W06A11.1-dependent muscle mitochondrial fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, mitophagy encapsulated the damaged mitochondria and dysfunctional mitochondria through the autophagy-lysosome pathway for either nutrient requirements or removing excessive ROS from tissues to maintain the mitochondrial dynamics. Under the conditions of over-nutrient (type 2 diabetes), inhibitions of autophagic flux and ROS generations due to impairment of mitochondrial respiration and fragmentation [ 66 , 67 ]. Natural products modulating mitophagy has been risen concern to improve the T2DM-associated mitochondrial dysfunctions ( Figure 2 ).…”
Section: Effects Of Natural Products On T2dm-related Tissues Through ...mentioning
confidence: 99%
“…In C. elegans drp-1 mutant, heat-stress-induced autophagy triggers swollen mitochondria that accumulate with intermediate autophagy structures (Figure 3). [58,59] Although the inactivation of the fusogenic protein mitofusin reduces the mitochondria size, it does not drive disappearance of autophagy intermediate around mitochondria. The authors concluded that Drp1 is involved in coordinating mitochondrial fission and autophagosome biogenesis in stress conditions.…”
Section: Drp1 Participates Directly To the Mitophagy Processmentioning
confidence: 99%
“…The authors concluded that Drp1 is involved in coordinating mitochondrial fission and autophagosome biogenesis in stress conditions. [58,59] Interestingly, the use of chemical stress on phosphorylation defective drp-1 C. elegans mutant as well as in the fis-1 mutant causes LC3 aggregate formation associated to mitochondria. [60] These aggregates are transient formation of LC3 labeled membrane intermingled with mitochondria and resemble autophagosome intermediates.…”
Section: Drp1 Participates Directly To the Mitophagy Processmentioning
confidence: 99%